Digital Public Relations Raspati Management di Tengah Pandemi Covid-19 - indah novianti; Dadi Ahmadi (Bandung Conference Series: Public Relations, 2022)
Abstract. Raspati Management is an entertainment management that presents many productions in the entertainment field, founded on the basis of a love for the art of music and accompanied by a high sense of social awareness. In Raspati Management there is an event organizer or commonly called EO such as making music events, Expo, Exhibitionx, productions houses, talents/artists. This research is entitled "Digital Public Relations Raspati Management in the Middle of the Covid-19 Pandemic (Case Study on Creating Events in Events promoted through the Raspati Management Official Youtube Account to increase brand engagement)". The purpose of this research is to find out how Raspati Management's Digital PR works in the midst of a pandemic and also what makes this research unique is the implementation of making events in events that are promoted through the youtube account of Raspati Management. This research uses a qualitative method with a case study approach that aims to find out how Raspati Management's digital PR works in promoting the creation of events in events through Youtube social media accounts. Supporting data in this study is the presence of two key informants and two supporting informants. Among them are Owner and Pr Raspati Management as key informants, and supporting informants are subscribers from Raspati Management's youtube account. The results of this study show that digital PR in an effort to promote events in events takes place effectively with the help of social media. Through social media, Raspati Management can develop its promotion process which usually uses conventional methods and then changes to the use of social media as the main means of promoting the events created. Abstrak. Raspati Management adalah sebuah management entertainment yang menyajikan banyak produksian di bidang entertain didirikan atas dasar kecintaan terhadap seni musik dan disertai rasa kepedulian sosial yang tinggi. Di dalam raspati management terdapat event organizer atau biasa di sebut EO seperti membuat event music, Expo, Exhibitionx, productions house, talent/artist. Penelitian ini berjudul “Digital Public Relations Raspati Management di Tengah Pandemi Covid-19 (Studi Kasus Pada Pembuatan Event dalam Event yang dipromosikan melalui Akun Youtube Raspati Management Official untuk meningkatkan brand engagement)”. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana cara kerja Digital PR Raspati Management ditengah pandemic dan juga yang menjadikan penelitian ini unik adalah dengan bentuk pengimplementasian pembuatan event dalam event yang dipromosikan melalui akun youtube dari Raspati Management. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus yang bertujuan untuk mencari tahu bagaimana cara kerja digital PR Raspati Managemennt dalam mempromosikan pembuatan event dalam event melalui akun sosial media Youtube. Data pendukung dalam penelitian ini adalah dengan adanya dua key informan dan dua informan pendukung. Diantaranya adalah Owner dan Pr Raspati Management sebagai key informan, dan informan pendukung adalah subscribers dari akun youtube Raspati Management. Hasil dari penelitian ini memperlihatkan bahwa dengan digital PR dalam upaya mempromosikan event dalam event berlangsung dengan efektif dengan dibantu melalui media sosial. Melalui media sosial tersebut, Raspati Management bisa mengembangkan proses promosi nya yang biasanya menggunakan cara konvensional lalu diubah dengan penggunaan media sosial sebagai sarana utama dalam mempromosikan event yang dibuat.